Development of a Society on Wheels Understanding the Rise of Automobile-dependency in China - Wang, Junxiu (Research Series on the Chinese Dream and China's Development Path, 2019)
Using quantitative research, this volume investigates the characteristics, problems and trends of the automobile society in China's mega cities and large cities. It also addresses topics related to cars and cities, traffic safety and cars' consumption. China has experienced more than 30 years of rapid economic development, and people's living conditions have greatly improved. One of the symbols of this is family-car ownership, which has increased year by year. China is rapidly becoming an automobile society like North America. But China has huge population and limited urban space, and most of the cities are deteriorating environmentally. Added to this are the low degree energy self-sufficiency and people's lack of awareness of traffic rules, all of which have brought various social problems, such as traffic congestion, lack of parking spaces, air pollution, energy shortage and frequent accidents. The volume presents a series of studies examining the characteristics and problems of China's automobile society development from the perspective of sustainable development. The reports in the volume are both academic and highly readable, making it an interesting resource for researchers and general readers alike. It offers insights into the trends and problems of private cars in China, as well as observations on China's social change through the unique medium of cars.